Analysis of the Inspectorate's Role in Resolving Audit Findings Using the Fraud Triangle Concept: Analisis Peran Inspektorat Dalam Menyelesaikan Temuan Audit Menggunakan Konsep Fraud Triangle - Cahyono, Ari Nugroho; Putri, Nia Rifanda; Islamiyati, Dian (Prosiding University Research Colloquium, 2023)
The function of the inspectorate as an internal auditor will be very important in detecting fraud and resolving fraud so that corruption can be prevented. This study aims to analyze the audit process carried out by the DIY Inspectorate in detecting fraud to resolve one of the audit findings and then analyze the case using the fraud triangle theory. The research was conducted at the DIY Inspectorate with a case finding on UPTD in 2017. The method used in this research is descriptive qualitative research with data collection techniques using interviews, and document analysis. In this study, the data validity test will use triangulation procedures, member cheking and data reliability. The first result of this study is that the DIY Inspectorate audit process begins with a routine inspection, then the auditor finds fraud through interviews with UPTD employees. The case is followed up by holding a case expose and formulating a solution to the case. The case was then resolved by the UPTD and the DIY Inspectorate. The second research result is a case analysis using the fraud triangle, case pressure because the vendor owner ordered employees not to pay the employment BPJS deposit. The opportunity occurred because the UPTD did not routinely check the employment BPJS payments of vendor employees. The rationalization in this case is that the vendor wants to get more profit than the employment BPJS money that should be paid.